2008
DOI: 10.1534/genetics.108.090340
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus (HERVK9) Structural Polymorphism With Haplotypic HLA-A Allelic Associations

Abstract: The frequency and HLA-A allelic associations of a HERVK9 DNA structural polymorphism located in close proximity to the highly polymorphic HLA-A gene within the major histocompatibility complex (MHC) genomic region were determined in Japanese, African Americans, and Australian Caucasians to better understand its human population evolutionary history. The HERVK9 insertion or deletion was detected as a 39 LTR or a solo LTR, respectively, by separate PCR assays. The average insertion frequency of the HERVK9.HG was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Reference DNA samples were obtained as previously described (19, 20) from 100 Japanese (Department of Legal Medicine, Shinshu University School of Medicine, Matsumoto , Nagano, Japan), 174 Australian–Caucasian (Department of Clinical Immunology and Biochemical Genetics , Royal Perth Hospital, Perth, Australia) from the seaside town of Busselton in Western Australia (http://www.busseltonhealthstudy.com/) and an HLA reference set of 67 B‐lymphoblastoid cell lines (European Collection of Cell Cultures) of different ethnic origins that were genotyped and/or serotyped at least for HLA alleles at the HLA ‐ DRB1 and ‐ DQB1 . The Caucasian DNA samples were also genotyped for DRB1, DRB3, DRB4 and DRB5 class II gene loci by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Reference DNA samples were obtained as previously described (19, 20) from 100 Japanese (Department of Legal Medicine, Shinshu University School of Medicine, Matsumoto , Nagano, Japan), 174 Australian–Caucasian (Department of Clinical Immunology and Biochemical Genetics , Royal Perth Hospital, Perth, Australia) from the seaside town of Busselton in Western Australia (http://www.busseltonhealthstudy.com/) and an HLA reference set of 67 B‐lymphoblastoid cell lines (European Collection of Cell Cultures) of different ethnic origins that were genotyped and/or serotyped at least for HLA alleles at the HLA ‐ DRB1 and ‐ DQB1 . The Caucasian DNA samples were also genotyped for DRB1, DRB3, DRB4 and DRB5 class II gene loci by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Some InDels are repetitive elements, such as Alu, HERV, L1 and SVA, or were generated by the influence of repetitive elements. 7,34,[80][81][82][83] INTRA-AND EXTRA-MHC GENE INTERACTIONS MHC genes do not function in isolation from other genes in the human genome, but they may interact with other genes inside (local or intra-MHC gene interaction) or outside the MHC region (global or extra-MHC gene interactions). The MHC gene interactions may be viewed as quantitative interactions between alleles at different loci that affect fitness or contribute to complex disease phenotypes (epistasis), 84,85 as simple statistical interactions between alleles at different loci (linkage disequilibrium or LD) as a consequence of functional selection or a hitchhiking effect, 86,87 as functional protein-binding interactions detected by two-hybrid, affinity capture or phage display methods, 88 or as protein-DNA interactions such as those between transcription factors and gene promoter and enhancer regions 89,90 or between replication protein factors and DNA replication sites and elements.…”
Section: Genomic Variationmentioning
confidence: 99%
“…A reference set of 100 Japanese population DNA samples genotyped at the loci of HLA‐A, Alu HJ, Alu HG, Alu HF, SVA HA, SVA HF and HERV K9.HG within the alpha block of the MHC class I genomic region (Fig. a) was obtained from 100 Japanese (the Department of Legal Medicine, Shinshu University School of Medicine, Matsumoto, Nagano, Japan (Moriyama et al ., )), 174 Australian Caucasians (Department of Clinical Immunology and Biochemical Genetics, Royal Perth Hospital, Perth, Western Australia) and 100 African Americans as previously described (Kulski et al ., , , ).…”
Section: Methodsmentioning
confidence: 99%
“…The allele and haplotype frequencies and structures of five MHC class I POALINs, Alu MICB, Alu TF, Alu HJ, Alu HG and Alu HF, were investigated in various Asian, European and sub‐Saharan African populations (Kulski & Dunn, ; Dunn et al ., , ; Tian et al ., ; Yao et al ., , 2010; Garcia‐Obregon et al ., ; Kulski et al ., ) and revealed genetic drift associated with bottlenecks in some Amerindian populations (Gomez‐Perez et al ., ). In addition, the association between five MHC class II POALINs ( Alu DPB2, Alu DQA2, Alu DQA1, Alu DRB1 and Alu ORF10) and HLA class II genes (Kulski et al ., ) and between the HLA‐A and HLA‐B class I genes and the structurally polymorphic MHC class I retroelements SVA (Kulski et al ., ) and HERV K9/solo MER9 (Kulski et al ., ) was investigated in Australian Caucasians, Japanese or African Americans (Kulski et al ., ). These studies showed that structurally polymorphic retroelements (SPRs) have specific relationships with particular HLA alleles and that they are informative ancestral markers in lineage (haplotype) analysis, hitchhiking effects, population and the evolution of diversity.…”
Section: Introductionmentioning
confidence: 99%